Mixing characteristics of elliptical throat sonic jets from orifice and nozzle. Issue 4 (19th May 2019) - Manigandan, S.; Vijayaraja, K.; Gunasekar, P.; Nithya, S.; Devipriya, J.; Ilangovan, N.
ABSTRACT: Aerodynamic mixing characteristics of the elliptical throat of the convergent divergent nozzle with an identical circular exit of aspect ratio 3 were studied computationally and experimentally. To determine the aerodynamic characteristics during mixing, the pressure distribution and pressure profiles were calibrated along the major and minor axes. The pressure variation in the orifice and nozzle shows that the energy decay in the nozzle dissipates faster than the jet from the orifice. Moreover, we visualised the pressure oscillation of the nozzle and orifices is closer to each other. In addition to that, we have also seen that the energy decay of both jets is approximately close to one another. The mixing promoting capability decreases as the area of the elliptical throat and the pressure gradient of the nozzle decrease. The computational results are evaluated with experimental values. The jet bifurcation is captured using StarCCM+.